Barriers and benefits of ICT adoption in the Nigerian construction industry. a comprehensive literature review - Moshood, Taofeeq D.; Nawanir, Gusman; Sorooshian, Shahryar; Fatimah, Mahmud; Adeleke, A. Q. (MDPI, 2020)
Information and Communication Technology (ICT) is seen as a way to enhance knowledge collection in the construction sector. Although the theoretical benefits of ICT implementation have been clarified, realizing such benefits is insufficient. This paper attempted a systematic analysis of the literature using ATLAS.ti 9 software to save, identify, and analyze this study’s data. A total of 102 articles were actively reviewed, including 82 Scopus journals and 20 conference papers published from 2003 to 2020. In this article, from a construction industry point of view, the ICT adoption process is considered as an interaction between technology, task, and an individual from a construction industry perspective. While ICT is acknowledged as a source of aggressive gain by both practitioners and scholars, ICT’s sole presence would definitely not guarantee achievement in the industry’s ICT approval. Companies cannot grasp the full benefits of ICT, except that users are able to adopt the technology. Hence, the issues related to ICT adoption need to be examined.